Do sheep of different coat colors kept in an equatorial semi-arid environment use solar orientation behavior for thermoregulation? - Morais, L. K.C.; Saraiva, E. P.; Sousa, W. H.; Maloney, S. K.; Hetem, R. S.; Santos, J. D.C.; Lima, L. A.A.; Moura, G. A.B. [UNESP]; Fonsêca, V. F.C. [UNESP] (Elsevier, 2024)
Shade-seeking behavior and body posture adjustments are key thermoregulatory strategies used by free-ranging animals to minimize heat absorption. We observed these behaviors in grazing sheep, analyzing their orientation relative to solar radiation. Over seven days, we monitored six predominantly black and six white crossbred lambs. We found that shade-seeking behavior was less frequent on cloudy days (p < 0.05), with sheep spending more time grazing. Neither the black or the white sheep altered their body orientation to minimize heat absorption, regardless of sunny or rainy conditions. In conclusion, this preliminary investigation showed that body axis orientation seems not to be employed by black and white hair coat sheep as thermoregulatory strategy when exposed to solar radiation in an equatorial semi-arid environment.
Keywords: Body posture; Lambs; Low latitude; Ruminants